Application of Arduino Programming Using ML8511 UV Sensor Hookup Guide to Learning the Effect of Ultraviolet’s Level - Nugroho Adi Pramono; Oktavia Ghaisyani; Bertha Anggita Purwandani; Fauzan Ibnu Sofyan (Journal of Disruptive Learning Innovation (JODLI), 2020)
This paper learn programming of an Arduino. This also explores on how it can be used as a tool for study and research works. Learn how to program with Arduino, connect the project board to software on your computer, create sensor with the decision making and memory storing abilities of the Arduino. The ML8511 UV sensor outputs an analog signal in relation to the amount of UV light it detects and the effect to human body if get UV light in levels. The result are from three different locations, such as two outdoor and indoor start from 6.30 a.m until 10.45 a.m. Data shows that in outdoor during early morning or late afternoon hours the sun's rays pass at a greater angle through the atmosphere. Much more UV radiation is absorbed and less reaches the Earth, on the contrary in indoor UV index was 0. UV levels are highest under cloudless skies, and cloud cover generally reduces a person's exposure. However, light or thin clouds have little effect and may even enhance UV levels because of scattering. Don't be fooled by an overcast day or a cool breeze! Even a long stay in open shade, for example between buildings, may give a sensitive person a sunburn on a day with high UV levels. Therefore, it is important to know effect of ultraviolet’s level, from application of Arduino Programming using ML8511 UV sensor simplify the research.Keywords: Sensor UV; ML8511; Arduino; UV lights; Software.